Perancangan Kearsipan Digital pada Sistem Administrasi Sekolah: Penelitian - Viola Oktarina; Dwi Riana; Yesita Astarina; Fepi Leisthari; Ratri Anjani Safitri; Syifa Anabilla (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Well-organized archive management plays an important role in supporting the smooth running of administrative activities in a school environment. At SD Negeri 10 Talang Kelapa, the filing system for incoming and outgoing letters is still carried out manually, by recording them in an agenda book and storing the documents in binder folders. This method causes the archive retrieval process to take a considerable amount of time and poses a risk of document damage. To address this issue, this study aims to design an electronic archive storage system by utilizing Microsoft Access 2013 to improve the overall archive management. The study uses a system development approach through the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The system is designed to include user login features, input forms for incoming and outgoing letters, archive data search, and the creation of digital archive reports. The design results show that the developed system can assist the process of recording, storing, and retrieving archives more easily and quickly. With the implementation of this system, it is expected that administrative activities at SD Negeri 10 Talang Kelapa can run more smoothly and in an orderly manner. In addition, the system also provides support in maintaining the completeness and security of archived documents so they can be accessed again when needed.